Circulating Tumor DNA Mutations in Progressive Gastrointestinal Stromal Tumors Identify Biomarkers of Treatment Resistance and Uncover Potential Therapeutic Strategies - Ko, Tun Kiat; Lee, Elizabeth; Ng, Cedric Chuan-Young; Yang, Valerie Shiwen; Farid, Mohamad; Teh, Bin Tean; Chan, Jason Yongsheng; Somasundaram, Nagavalli (Frontiers in Oncology, 2022)
Liquid biopsy circulating tumor DNA (ctDNA)-based approaches may represent a non-invasive means for molecular interrogation of Gastrointestinal Stromal Tumors (GISTs). We deployed a customized 29 gene Archer® LiquidPlex™ targeted panel on 64 plasma samples from 46 patients. The majority were known to harbor KIT mutations (n = 41, 89.1%), while 3 were PDGFRA exon 18 D842V mutants and the rest (n = 2) were wildtype for KIT and PDGFRA. In terms of disease stage, 14 (30.4%) were localized GISTs that had undergone complete surgical resection while the rest (n = 32) were metastatic. Amongst ten patients, including 7 on tyrosine kinase inhibitors, with evidence of disease progression at study inclusion, mutations in ctDNA were detected in 7 cases (70%). Known somatic mutations in KIT (n = 5) or PDGFRA (n = 1) in ctDNA were identified only amongst 6 of the 10 patients. These KIT mutants included duplication, indels and single nucleotide variants. The median mutant AF in ctDNA was 11.0% (range 0.38%–45.0%). In patients with metastatic progressive KIT-mutant GIST, tumor burden was higher with detectable KIT ctDNA mutation than in those without (median, 5.97 cm vs 2.40 cm, p = 0.0195). None of the known tumor mutations were detected in ctDNA for localized cases (n = 14) or metastatic cases without evidence of disease progression (n = 22). In patients with serial samples along progression of disease, secondary acquired mutations, including a potentially-actionable PIK3CA exon 9 c.1633G>A mutation, was detected. ctDNA mutations were not detectable when patients responded to a switch in TKI therapy. In conclusion, detection of GIST-related mutations in ctDNA using a customized targeted NGS panel represents an attractive non-invasive means to obtain clinically-tractable information at the time of disease progression.